2002
DOI: 10.3349/ymj.2002.43.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure Associated with a Minimal Change Nephrotic Syndrome in a Systemic Lupus Erythematosus Patient

Abstract: In systemic lupus erythematosus (SLE), acute renal failure (ARF) is usually associated with severe lupus nephritis and ARF associated with other glomerular diseases is extremely rare. We recently encountered a patient with ARF that was associated with a minimal change nephrotic syndrome (MCNS) in SLE. A 41-year-old woman presented with a nephrotic syndrome and ARF. She fulfilled four of the American College of Rheumatology criteria for the classification of SLE. However, a renal biopsy revealed that there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Most patients with lupus podocytopathy present with nephrotic syndrome, some patients also display acute kidney injury. [21][22][23] The treatment regimen for lupus podocytopathy reported in the literature is similar to that used for primary MCD or FSGS, with glucocorticoids being the most widely prescribed agents. Recently, clinical practice guidelines for lupus nephritis have recommended glucocorticoid monotherapy or glucocorticoid plus immunosuppressant therapy for the treatment of lupus podocytopathy with nephrotic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with lupus podocytopathy present with nephrotic syndrome, some patients also display acute kidney injury. [21][22][23] The treatment regimen for lupus podocytopathy reported in the literature is similar to that used for primary MCD or FSGS, with glucocorticoids being the most widely prescribed agents. Recently, clinical practice guidelines for lupus nephritis have recommended glucocorticoid monotherapy or glucocorticoid plus immunosuppressant therapy for the treatment of lupus podocytopathy with nephrotic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…First, lupus podocytopathy patients present with a high incidence of AKI without overt hematuria. The incidence of AKI in lupus podocytopathy patients was reported to be as high as 57% (8,29,30). Overall, 34% of the patients in this study were found to have AKI, and among them only a small proportion showed mild microscopic hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…Acute renal failure (ARF) in the setting of minimal change disease occurs in one-quarter of such patients. Lupus podocytopathy has also been reported as a complication of ARF [20], and nephrotic lupus podocytopathy elevated serum creatinine compared with non-nephrotic lupus podocytopathy [3]. The pathophysiological basis of ARF in minimal change disease is not understood.…”
Section: Discussionmentioning
confidence: 98%